2012
DOI: 10.1186/1749-8090-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Auditory stimulation of opera music induced prolongation of murine cardiac allograft survival and maintained generation of regulatory CD4+CD25+ cells

Abstract: BackgroundInteractions between the immune response and brain functions such as olfactory, auditory, and visual sensations are likely. This study investigated the effect of sounds on alloimmune responses in a murine model of cardiac allograft transplantation.MethodsNaïve CBA mice (H2k) underwent transplantation of a C57BL/6 (B6, H2b) heart and were exposed to one of three types of music--opera (La Traviata), classical (Mozart), and New Age (Enya)--or one of six different single sound frequencies, for 7 days. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Furthermore, specific type of auditory enrichment used here also affected the immune genes expression in zebrafish vs. unexposed controls ( Fig. 3A ), similar to music effects reported earlier in rodents ( Lu et al, 2010 ; Uchiyama et al, 2012 ). Here, fish exposed to auditory enrichment showed lower expression of some pro-inflammatory genes (IL-1β and IFN-γ), but without affecting anti-inflammatory genes IL-10 and IL-4 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, specific type of auditory enrichment used here also affected the immune genes expression in zebrafish vs. unexposed controls ( Fig. 3A ), similar to music effects reported earlier in rodents ( Lu et al, 2010 ; Uchiyama et al, 2012 ). Here, fish exposed to auditory enrichment showed lower expression of some pro-inflammatory genes (IL-1β and IFN-γ), but without affecting anti-inflammatory genes IL-10 and IL-4 ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The zebrafish (Danio rerio) is a widely used animal model organism in neuroscience research ( Papoutsoglou et al, 2007 ; Sicca et al, 2016 ; Levitas-Djerbi & Appelbaum, 2017 ; Uchiyama et al, 2012 ; Kalueff et al, 2013 ). They are genetically and physiologically similar to others vertebrates, such as rodents and humans ( Howe et al, 2013 ), and possess a well-described behavioral repertoire ( Kalueff et al, 2013 ) and stress neuroendocrine axis ( Stewart et al, 2014 ; Kalueff, Stewart & Gerlai, 2014 ; Alsop & Vijayan, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several experimental studies in healthy rodents and in rodent disease models found similar effects as reported in humans, such as enhanced spatial ability (Xing et al, 2016c), improved neuroplasticity (Kirste et al, 2015), anxiety reduction (Escribano et al, 2014), blood pressure lowering (Sutoo and Akiyama, 2004), and increasing immune function (Uchiyama et al, 2012; Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 70%
“…Moreover, in another study, it was shown to alleviate GVHD via increasing splenic regulatory T cell [ 16 ]. Based on our previous data, it can be reasoned that inducible CD4 + Foxp3 + Treg do not disappear in a short period of time [ 17 , 18 ]. From the findings in this study that demonstrate that the general structure of the allograft was maintained even three weeks after termination of TM administration, it can be concluded that TM may generate CD4 + Foxp3 + regulatory T cells that infiltrate transplanted cardiac allografts and that greater aggregation of these cells around coronary arteries may lead to the prolongation of allograft survival.…”
Section: Discussionmentioning
confidence: 99%